Community Development Agreement : Model Regulations and Example Guidelines - Otto, James M. (World Bank, Washington, DC, 2017)
Mines have the potential to impact communities and such impacts can be both positive and negative. Historically, mines have played an important role in impacted communities but that role usually ended with the closure of the mine. More recently, there is a strong interest by governments, communities and mining companies in the sustained development of mine impacted communities. The World Bank Group (WBG) has a role to play in mining-led development at both the national and community level. The purpose of this report is to provide draft model community development agreement regulations suitable for adoption into legislation or which can be modified for use as guidelines. It is not the intent of this report to suggest that every nation should adopt the model legislation, rather the model legislation is simply another tool that governments can consider as part, or not, of their development strategy. In many nations, the promulgation of regulations is easier than introducing a new or amended mining law, and thus, model regulations were drafted rather than model mining law provisions. This report is the product of a phased project approach. Phase one was designed to prepare a draft set of Community Development Agreement (CDA) regulations in consultation with and benefiting from technical experts. Phase two, of which this report is a part, was intended to obtain feedback from a broad spectrum of stakeholders including governments, private sector, non-governmental organizations, civil society and development experts.